The perception of gender stereotypes in today’s life / Nur Rina Irdina Rosli…[et.al] - Rosli, Nur Rina Irdina; Saidin, Nur Fazlinda; Jalaludin, Ahmad Adli; Ibrahim Sukri, Imran Syahril (Faculty of Communication & Media Studies, 2019)
Between men and women, there are so many differences. To some dimension, the differences captured in the stereotypical images between those two genders. Stereotypes about the way men and women behave and think are shared extensively. Despite, stereotypical forecasts not only reflect actual differences, but also impact how they define themselves and how they are treated by others. The purpose of this study is to examine the general perceptions of Malaysians regarding Gender Stereotypes between men and women towards their roles in everyday life. To examine whether the roles of men and women disputed or not from the selected sample, an online form from Google Online Survey has been distributed to all social medias’ platform from various people from various age to gain the perception of Malaysians regarding the gender stereotypes and it involves 633 respondents. In order to collect the data, researchers have referred to Krejcie and Morgan table (1970), 30 million population in Malaysia or 12 million respondents can be equivalent to 384 sample of respondents with 95% confidence to represent the data. The findings were discussed in relation to socialization, values and norms of the Malay society. In the end, researchers knew that the people’s perception of gender stereotypes in today’s life is no longer relevant and must be re-looked in order to live in a harmony and peaceful life. Overall the results showed that respondents believed that men and women should be treated equally (M=3.56) Additionally, respondents also strongly disagree with gender stereotypes among men nowadays (M=1.63) and gender stereotypes among women in today’s life (M=1.49)